The Impact of the 1990 Dilan Film on the Behavior of Students of SMA Negeri 1 Bengkulu Selatan - Gading Abiemayu Baskara; Sri Narti; Yanto Yanto (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
This thesis is entitled The Impact of the 1990 Dilan Film on the Behavior of the Students of SMA Negeri 1 Bengkulu Selatan. This study aims to determine the impact of the Dilan film on the behavior of students in SMA Negeri 1 South Bengkulu. This research uses quantitative research. The object of this research is the students of SMA Negeri 1 South Bengkulu, the method used by the author in this research is survey and documentation, the theory used in this research is the theory of Television Watching Pattern and theory Attribution. The data analysis technique used is the Likert Scale where the author uses the scale to determine the results of the answers from the respondents. The next stage in this test the author uses the correlation coefficient test to measure the strength of the relationship between two variables based on the Correlation Coefficient Interpretation, after that the Relationship Significance and Determination Coefficient test is carried out to see the effect of the Dilan film on the students of SMA Negeri 1 South Bengkulu. In this study the authors used the SPSS 26 application for the test. Based on the results of research and discussion on the Impact of the 1990 Dilan Film on the Behavior of the Students of SMA Negeri 1 South Bengkulu, the relationship between the two variables is very low, insignificant and not unidirectional. This is shown from the results of the Correlation Coefficient test, the value obtained is -0,202 with a significance number of 0.05 (very low). So it can be concluded that there is no impact on the behavior of the students of SMA Negeri 1 South Bengkulu.